Contos fantásticos brasileiros: interrelações entre a leitura e as características e convenções genológicas - Egiert, Suéllen de Fátima (2013)
Regarding the emphasis that the reception takes in modern studies on literary genres, this dissertation presents an interface study between reading and genology, with the main goal to reflect about the formation possibility of the fantastic literary genre in its features and aesthetic-literaries conventions, relate to a particular conception of reading, that means, the extent to which the reception is part of the conception of literary genre and how gender issues affect or require a way of reading the narrative. The methodology contemplates a literature review about the conceptions of reading and reader in theories of structuralism, the Reception Aesthetics and Semiotics; specification concepts regarding archtextuality and genology; studies on descriptions and definitions of the fantastic in literature of theorists like Todorov, Roas, Fernández, Alazraki and Volobuef, in whose were recognized the peculiarities of literary discourse of the fantastic genre which reading and the reader are considered. The literary corpus includes the Brazilians fantastic tales "O pirotécnico Zacarias" by Murilo Rubião, and "Sala de Armas" by Nelida Piñon, whose analysys emphasized the characteristics and aesthetic conventions recurring in texts of fantastic literature, identifying it the marks of an implicit reception in the narrative, that means, a projection of a virtual reader (narratee, implied reader or reader model) that cooperates or enhances the characteristics of the appealing structure of stories The results indicate that the fantastic gender set up historically as having literary-aesthetic procedures guided by the reading concept as a communicative and cooperative process, which can be seen in the analysis of Brazilian fantastic tales selected.